Ccr6 Deficiency Attenuates Spontaneous Chronic Colitis in Winnie - Ranmali Ranasinghe; Ruchira Fernando; Agampodi Promoda Perera; Madhur Shastri; Waheedha Basheer; Paul Scowen; Terry Pinfold; Rajaraman Eri (Gastrointestinal Disorders, 2020)
Background: The immune-modulator behaviour of the CCR6/CCL20 axis in multi -system pathophysiology and molecular signalling was investigated at two clinically significant time points, using a Ccr6—deficient mouse model of spontaneous colitis. Methods:Four groups of mice, (C57BL/6J, Ccr6−/− of C57BL/6J, Winnie ×Ccr6−/−and Winnie) were utilized and (I) colonic clinical parameters (2) histology of colon, spleen, kidney and liver (3) T and B lymphocyte distribution in the spleen and MLN by flowcytometry (5) colonic CCL20, phosphorylated PI3K and phosphorylated Akt expression by immunohistochemistry and (6) colonic cytokine expression by RT-PCR were evaluated. Results: CCR6 deficiency was shown to attenuate inflammation in the spleen, liver and gut while renal histology remained unaffected. Marked focal lobular inflammation with reactive nuclear features were observed in hepatocytes and a significant neutrophil infiltration in red pulp with extra medullary hemopoiesis in the spleen existed in Winnie. These changes were considerably reduced in Winnie ×Ccr6−/−- with elevated goblet cell numbers and mucus production in the colonic epithelium. Conclusions: Results indicate that Ccr6- deficiency in the colitis model contributes towards resolution of disease. Our findings demonstrate an intricate networking role for CCR6 in immune activation, which is downregulated by Ccr6 deficiency, and could provide newer clinical therapies in colitis.